2022
DOI: 10.5530/pj.2022.14.24
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, Chemical Composition and Antioxidant Activity of Phenolic Compounds from Moroccan Satureja nepeta L.

Abstract: Ethanol, Quercetin was supplied by China Institute for Drugs and Biological Products Identification (Beijing, China), and the purity is over 98%. sodium carbonate, sodium nitrite, aluminum trichloride, anthrone, sulfuric acid, disodium phosphate Folin-Ciocalteu reagent and 1,1-diphenyl-2-picrylhydrazyl radical (DPPH), ABTS (2,2′-Azinobis-(3ethylbenzthiazoline-6-sulfonic acid), ferric chloride (FeCl 3 ) and Ascorbic acid were purchased from Sigma (St. Louis, MO, USA). All the other reagents were of analytical g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…A previous study characterized the phenolic compounds of S. nepeta , for the aqueous extract by HPLC-UV. 1 Among the various compounds characterized by HPLC-UV (rutin, quercetin, catechin, caffeic acid, vanillic acid, ferulic acid, and gallic acid), we found that quercetin, catechin, and gallic acid were the 3 major compounds representing more than 60% of the total composition ( Table 1 ). These 3 compounds are known for their anti-inflammatory effect.…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…A previous study characterized the phenolic compounds of S. nepeta , for the aqueous extract by HPLC-UV. 1 Among the various compounds characterized by HPLC-UV (rutin, quercetin, catechin, caffeic acid, vanillic acid, ferulic acid, and gallic acid), we found that quercetin, catechin, and gallic acid were the 3 major compounds representing more than 60% of the total composition ( Table 1 ). These 3 compounds are known for their anti-inflammatory effect.…”
Section: Resultsmentioning
confidence: 88%
“…In fact, studies have demonstrated that the major active compounds of S. nepeta have significant therapeutic potential for inflammatory bowel diseases such as Crohn’s disease and irritable bowel syndrome. 1 , 28 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations